In situ formation and photo patterning of emissive quantum dots in small organic molecules. Issue 25 (10th June 2015) - Bansal, Ashu K.; Sajjad, Muhammad T.; Antolini, Francesco; Stroea, Lenuta; Gečys, Paulius; Raciukaitis, Gediminas; André, Pascal; Hirzer, Andreas; Schmidt, Volker; Ortolani, Luca; Toffanin, Stefano; Allard, Sybille; et al.
Abstract : Laser patterning of luminescent metal selenide nanoparticles in organic semiconductor films is demonstrated by thermal decomposition of a precursor. Abstract : Nanostructured composites of inorganic and organic materials are attracting extensive interest for electronic and optoelectronic device applications. Here we report a novel method for the fabrication and patterning of metal selenide nanoparticles in organic semiconductor films that is compatible with solution processable large area device manufacturing. Our approach is based upon the controlled in situ decomposition of a cadmium selenide precursor complex in a film of the electron transporting material 1, 3, 5-tris( N -phenyl-benzimidazol-2-yl)-benzene (TPBI) by thermal and optical methods. In particular, we show that the photoluminescence quantum yield (PLQY) of the thermally converted CdSe quantum dots (QDs) in the TPBI film is up to 15%. We also show that laser illumination can form the QDs from the precursor. This is an important result as it enables direct laser patterning (DLP) of the QDs. DLP was performed on these nanocomposites using a picosecond laser. Confocal microscopy shows the formation of emissive QDs after laser irradiation. The optical and structural properties of the QDs were also analysed by means of UV-Vis, PL spectroscopy and transmission electron microscopy (TEM). The results show that the QDs are well distributed across the film and their emission can be tuned over a wide range by varying the temperature or irradiated laser power on the blend films. Our findings provide a route to the low cost patterning of hybrid electroluminescent devices.